Neural regions discriminating contextual information as conveyed through the learned preferences of others - Lee, Su Mei; McCarthy, Gregory (Frontiers in Human Neuroscience, 2015)
The human brain consists of a network of regions that are engaged when one observes the movements of others. Observing unexpected movements, as defined by the context, often elicits greater activity, particularly in the right posterior superior temporal sulcus (pSTS). This implies that observers use contextual information to form expectations about an agent’s goal and subsequent movements. The current study sought to identify regions that support the formation of these context-dependent expectations, with the pSTS being one candidate, given the consistent contextual modulation of its activity. We presented participants with fictitious individuals who had emotion-dependent food preferences, and instructed participants to indicate which food they expected each individual to choose based on the individual’s current emotional state. Each individual’s preference and emotional state therefore created a context that informed the observer’s expectation of the individual’s choice. Multi-voxel pattern analysis was used to assess if these different contexts could be discriminated in the pSTS and elsewhere in the brain. No evidence for context discrimination was found in the pSTS. Context discrimination was found instead in a network of other brain regions including the anterior medial prefrontal cortex, bilateral parietal cortex, left middle temporal gyrus and left anterior temporal lobe, which have been previously associated with context processing, and semantic and memory retrieval. All together, these regions possibly support the formation of context-dependent expectations of an agent’s goal.